Character Networks for Narrative Generation - Sack, Graham (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2012)
In this position paper, the author proposes the use of social networks of characters as an AI narrative generation mechanism. The first part of the paper offers examples of recent research by literary critics on the relationship between character networks and narrative structure. The second part of the paper offers a simple example of story generation based on a structural balance network model.